Regulatory Limbo and Political Signaling in Digital Governance: Lessons from Indonesia and the United Kingdom - Rizky Pratama Azari; Salwa Zahratun Nisa; Irfan Saputra (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the institutional weaknesses of digital governance in Indonesia through the conceptsof regulatory limbo and political signaling by comparatively analyzing the regulatory frameworks of Indonesia and the United Kingdom. Although Indonesia enacted Law No. 27 of 2022 on Personal Data Protection alongside several related digital regulations, the implementation of these legal norms remains constrained by fragmented oversight, limited enforcement capacity, and the absence of a fully operational independent supervisory authority. Employing normative legal research with a functional comparative approach, this study analyzes the relationship among legal norms, institutional structures, and state responses to digital threats including major data breaches, cybersecurity incidents, and the Grok AI controversy. The findings indicate that Indonesia'sdigital governance challenges reflect a condition of enforcement deficit, in which legal norms formally exist but are not supported by sufficiently effective enforcement and supervisory mechanisms. This condition contributes to reactive and symbolic policy responses that prioritize immediate control measures over long-term structural reform. By contrast, the United Kingdom adopts a more institutionalized and risk-based regulatory approach through independent oversight mechanisms and procedural accountability under the Online Safety Act 2023. This study argues that effective digital governance depends not solely upon the existence of formal legal regulation, but also upon institutional capacity, coherent enforcement structures, and adaptivesupervisory mechanisms capable of responding to emerging technological risks.